Traditional Medicines, Collective Negotiation, and Representations of Risk in Indian Cancer Care. (January 2013) - Broom, Alex F.; Doron, Assa
Cancer is emerging as a key disease in India, but there has been virtually no research exploring understandings of cancer and practices of communication within oncology settings. This is despite the fact that the Indian context presents clinicians, patients, and family members with a range of unique challenges, including those related to disease awareness, interpersonal dynamics, and the use of traditional, complementary, and alternative medicines (TCAM). Drawing on a series of qualitative interviews with 22 Delhi-based oncology clinicians, in this article we examine clinicians' accounts of communication with their cancer patients. The interviews reveal the challenges of communication given cancer's relative novelty, cultural practices around collective negotiation, and rhetorical practices evident in advice-giving regarding TCAM. We conclude that with cancer set to become a major burden in India, research exploring competing forms of expertise, the politics of representation, and the nexus between traditional beliefs and techno-scientific development is urgently needed.